(untitled) (Training and Practice : Journal of Educational Sciences, 2012)
The author in her thesis categorises the functions of adult education from the individual’s point of view, whether it focuses on the labour market or the individual’s life quality. Both function groups allow creating a function of a new aspect, i.e. the establishment of the comfort feeling. According to Kispálné Horváth, Mária comfort feeling is an umbrella term including the following dimensions: feeling of safety, lifestyle, time structure, psycholigical dispositions, social relations and the usability of knowledge. The author analyses the positive effects of formal adult education on several segments of comfort feeling, as well as presents the potential negative effects of formal adult education.